Hypoplastic left heart syndrome: current perspectives - Greenleaf, Christopher E. (Transl Pediatr, 2016)
Since the first successful intervention for hypoplastic left heart syndrome (HLHS) was undertaken by Norwood in 1983, there have been many advancements in the pre-, intra-, and postoperative care of these children for a diagnosis that just 25 years ago was almost certainly a fatal one. This paper aims to describe the most recent trends and perspectives on the treatment of HLHS. In particular, we will discuss the five current options for HLHS, including Norwood stage I as the beginning to 3-stage palliation, transplant, true hybrid, hybrid-bridge-to-Norwood, and compassionate care.